Challenges in transferring knowledge between scales in coastal sediment dynamics - Gallop, Shari L.; Collins, Michael; Pattiaratchi, Charitha B.; Eliot, Matthew J.; Bosserelle, Cyprien; Ghisalberti, Marco; Collins, Lindsay B.; Eliot, Ian; Erftemeijer, Paul L. A.; Larcombe, Piers; Marigómez, Ionan; Stul, Tanya; et al. (Frontiers in Marine Science, 2015)
‘Packaging’ coastal sediment transport into discrete temporal and spatial scale bands is necessary for measurement programs, modelling, and design. However, determining how to best measure and parameterize information, to transfer between scales, is not trivial. An overview is provided of the major complexities in transferring information on coastal sediment transport between scales. Key considerations that recur in the literature include: interaction between sediment transport and morphology; the influence of biota; episodic sediment transport; and recovery time-scales. The influence of bedforms and landforms, as well as sediment-biota interactions, varies with spatio-temporal scale. In some situations, episodic sediment dynamics is the main contributor to long-term sediment transport. Such events can also significantly alter biogeochemical and ecological processes, which interact with sediments. The impact of such episodic events is fundamentally influenced by recovery time-scales, which vary spatially. For the various approaches to scaling (e.g., bottom-up, aggregation, spatial hierarchies), there is a need for fundamental research on the assumptions inherent in each approach.